Poverty Reduction Strategy Based on Family Empowerment in the Perspective of Islamic Law - Anisul Fuad (Universitas Islam Negeri Walisongo Semarang, 2022)
The mandate to eradicate poverty is part of the mission of the presence of Islam as a religion of rahmatan lil 'alamin. Poverty alleviation is one of the main aspects of development, as stated in the Sustainable Development Goals (SDGs). This study aims to determine two things: (1) What is the poverty alleviation strategy based on family empowerment in Indonesia?; (2) What is the perspective of Islamic law on poverty alleviation strategies through family empowerment? Poverty alleviation policies in Indonesia are operationalized in various forms of activity, including targeting family empowerment programs. This study uses a literature review method. Based on the results of the analysis, it was found that the poverty alleviation strategy through family empowerment was in three main policy groups, namely the social assistance and protection-based policy group, the participatory empowerment-based policy group, and the micro and small business empowerment-based policy group. Both strategies are in line with Islamic teachings, which contain poverty alleviation.